2021
DOI: 10.3390/pathogens10010071
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Identify New Anti-Filarial Leads to Treat River Blindness, a Neglected Tropical Disease

Abstract: Filarial worms cause multiple debilitating diseases in millions of people worldwide, including river blindness. Currently available drugs reduce transmission by killing larvae (microfilariae), but there are no effective cures targeting the adult parasites (macrofilaricides) which survive and reproduce in the host for very long periods. To identify effective macrofilaricides, we carried out phenotypic screening of a library of 2121 approved drugs for clinical use against adult Brugia pahangi and prioritized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 116 publications
2
22
0
Order By: Relevance
“…To identify repurposed drugs for use as anti-filarial agents, we first screened a library of FDA-approved drugs with adult B. pahangi in vitro and found that PVP was the most potent compound among the 2200 that were tested; it reduced motility of B. pahangi with an IC 50 in the sub-nanomolar range (0.3 nM) [11]. This study extends the initial observation as well as presents the comparative outcomes of testing PVP and several of its analogs on Brugia and other filarial parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify repurposed drugs for use as anti-filarial agents, we first screened a library of FDA-approved drugs with adult B. pahangi in vitro and found that PVP was the most potent compound among the 2200 that were tested; it reduced motility of B. pahangi with an IC 50 in the sub-nanomolar range (0.3 nM) [11]. This study extends the initial observation as well as presents the comparative outcomes of testing PVP and several of its analogs on Brugia and other filarial parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we screened a library of FDA-approved drugs and identified the anthelminthic drug, pyrvinium pamoate (PVP), as a potent hit in in vitro filarial worm assays [11]. PVP has been used over the last 50 years to treat pinworm infections (enterobiasis) in children; however, it is not readily bioavailable as it is not appreciably absorbed by the gastrointestinal tract [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…worms, which are very sluggish even in the absence of drug treatment, and in vitro drug screening with O . ochengi continues to use visual scoring, albeit with a more complex six-point categorisation than we applied here ex vivo [ 77 ]. The fact that subjective motility scoring by technicians blinded to treatment group indicated clear dose-dependent effects of emodepside against adult worms supports the reliability of this readout.…”
Section: Discussionmentioning
confidence: 99%
“…Early iterations of image-based screening focused on gross worm movement, using a number of different approaches to quantify movement, including sparse measures of optical flow and frame-by-frame pixel variation [3][4][5][6][7]. Optical flow was found to be robust to a number of diverse nematode and flatworm parasites and has been the basis for some of the largest phenotypic screening efforts to-date [8][9][10]. Other developments in high-content imaging, sometimes combined with the employment of fluorescent stains to reveal fine-scale phenotypes, now allow for the quantification of detailed morphological and molecular features that can be used for image-based classification strategies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%